Sistem Informasi Penyewaan Gedung Olahraga Berbasis Web - Ratama, Niki; Muhajar, Aldy; Indrawan, Dicky; Yanto, Galih Ferdhi; Nurhidayat, Rizki; Nirmala, Endar (Program Studi Teknik Informatika Universitas Pamulang, 2022)
The Sports Building (GOR) is a place made to carry out sports activities, but most of these rental places do not have a website to make it easier to rent. In addition, by utilizing existing technology to make it more utilized, it is hoped that it can fully reach people who use manual methods when renting sports halls. The program that has been made will be researched and tested to identify its strengths and weaknesses, in this case an assessment is needed to perfect and perfect the program and system, then introduce and test the new system. This stage is carried out after the project is completed. Making this website system using MySQL as information storage and the language used in programming is PHP, HTML CSS. in making this application using the watterfall methodology. The waterfall methdology is a project management approach that emphasizes a linear progression from start to finish of a project. This methodology, often used by engineers, is preloaded to rely on careful planning, detailed documentation and sequential execution. This software was created to be able to overcome the problems that exist in the rental of sports buildings manually.